How ‘going online’ mediates the challenges of policy elite interviews - Karin Vaagland (Humanities & Social Sciences Communications, 2024)
Abstract Relevant data on sensitive and politicised political processes might be difficult to obtain and is sometimes even purposely hidden from the public domain. Policy elite interviews constitute crucial sources of information in policy research. However, there are significant challenges associated with ‘researching up’ which sets elite interviews apart from other interview methods. Although there is a great deal of literature concerning interviews conducted via phone or audio-visual computer programs, the implications of conducting policy elite interviews online have received surprisingly little attention. This paper discusses how going online can mediate the main challenges associated with policy elite interviews. These challenges include barriers to gaining access, dealing with biased information, and problems concerning positionality. Based on a least likely case to access relevant data, this paper reflects on personal experience from 20 online interviews with European Commission representatives on policy responses to the 2015 migration crisis. The paper concludes that the online format facilitated unique insights into a highly controversial issue area.